INTERAKSI SOSIAL ASOSIATIF ANTAR PENGHUNI ASRAMA MAHASISWA KABUPATEN LANDAK DI KOTA PONTIANAK - Putra, Andika Aliansya; Imran, Imran; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study entitled "Associative social interaction between residents of the hedgehog district student dormitories in Pontianak city". A common problem in this study is "How are associative social interactions between residents of the hedgehog district student dormitories in Pontianak?". Sub research problems are as follows: 1) How is associative social interaction in the form of cooperation between residents of the hedgehog district student dormitories in the city of Pontianak; 2) How is associative social interaction in the form of accommodation between residents of the hedgehog district student dormitories in Pontianak city? The method used is a qualitative method. Sources of data in this study are primary data and secondary data. Data collection techniques used are observation techniques, direct communication and documentary studies (bibiliographic) with data collection tools in the form of observation, interviews and documentation. The results showed that: 1) Associative social interaction in the form of cooperation between residents of the Landak district student dormitory in the city of Pontianak, namely mutual cooperation carried out in the form of cleaning in the dormitory and outside the dormitory environment, then help please be shown by helping friends who are trouble and visit a friend who is sick. 2) Associative social interactions in the form of accommodation between residents of the Landak Regency student dormitory in Pontianak City, namely a compromise with routine joint evaluation activities, mutual tolerance between residents, and arbitration, namely by mediating in solving problems.Keywords: Cooperation, Acomodation, Landak Dormitory Residents